Is It Effective to Perform Two More Prostate Biopsies According to Prostate-Specific Antigen Level and Prostate Volume in Detecting Prostate Cancer? Prospective Study of 10-Core and 12-Core Prostate Biopsy - Yoon, Byung II; Shin, Tae Seung; Cho, Hyuk Jin; Hong, Sung-Hoo; Lee, Ji Youl; Hwang, Tae-Kon; Kim, Sae Woong (Urology Journal, 2012)
PURPOSE: To evaluate the effectiveness of 2 more core prostate biopsy protocol in detecting the prostate cancer (PCa) by comparing 10-core prostate biopsy with 12-core according to the prostate-specific antigen (PSA) level and the prostate volume. MATERIALS AND METHODS: A total of 474 men with elevated serum levels of PSA between 2.5 and 20.0 ng/mL, regardless of abnormal finding on digital rectal examination and transrectal ultrasonography, received transrectal ultrasound-guided prostate biopsies. The patients were prospectively randomized to undergo 10-core (group 1, n = 351) or 12-core (group 2, n = 123) biopsy. The PCa detection rates were assessed and compared according to the serum level of PSA and prostate volume. RESULTS: Of 474 men, 128 (27.0%) were diagnosed with PCa. The PCa detection rates of 10-core and 12-core biopsies were 26.4% and 28.4%, respectively (P = .378). There was no difference in cancer detection rates according to PSA level in both groups. Comparing the cancer detection rates according to the prostate volume (< 40 mL and ≥ 40 mL), the patients with prostate volume ≥ 40 mL showed higher cancer detection rates in 12-core biopsy group (26.9%) compared with 10-core biopsy group (16.4%) (P < .05). CONCLUSION: The overall cancer detection rates showed no differences in both groups. But the 12-core biopsy was a more efficient method in men with a prostate volume of ≥ 40 mL, compared to the 10-core biopsy.